Adhesive Capsulitis of the Shoulder Joint: Value of Glenohumeral Distance on Magnetic Resonance Arthrography. Issue 1 (January 2017) - Lee, Kyu Hong; Park, Hee Jin; Lee, So Yeon; Youn, In Young; Kim, Eugene; Park, Jai Hyung; Park, Se Jin
Abstract : Objective: To evaluate the usefulness of glenohumeral distance (GHD) on axial images of magnetic resonance (MR) arthrography for diagnosis of adhesive capsulitis and to compare this finding with previously reported classic MR arthrographic findings of adhesive capsulitis. Materials and Methods: Our study was approved by the institutional ethical review board of our institute. We evaluated 41 patients (M-F, 35:6; mean age, 46 years; adhesive capsulitis, 21; no adhesive capsulitis, 20) who underwent MR arthrography. Two radiologists measured GHD, width of the axillary recess, and capsular thickness in consensus. The GHD was measured from the subchondral bone of the glenoid fossa to the subchondral bone of the humeral head at the level of the midline of the humeral head. Glenohumeral distance (anterior, middle, posterior, and mean), width of the axillary recess, and capsular thickness (anterior, posterior, and mean) were compared in the adhesive capsulitis and no adhesive capsulitis groups using the Mann-Whitney U test. Results: The mean GHD of the no adhesive capsulitis group was longer than that of the adhesive capsulitis group. The length differences were statistically significant ( P < 0.05). The mean width of the axillary recess of the no adhesive capsulitis group was significantly wider than that of the adhesive capsulitis group ( P < 0.001). The mean capsular thickness of the no adhesive capsulitis group was significantly thinner than that in the adhesive capsulitis group ( P = 0.001). Conclusions: A decreased GHD on MR arthrography can be another useful feature to diagnose adhesive capsulitis in addition to previously presented radiologic features such as capsular thickening and reduced axillary recess capacity.